GeoWorldSim: Cross-Modal Geographic World Modeling for Embodied Urban Navigation via Diffusion-Based Spatial Scene Generation - Karan Dutta; Leif R. Mills; Pascal Terry (Computational Intelligence Systems, 2026)
Embodied urban navigation requires agents to perceive, reason, and act within complex, dynamic city environments that are inherently multimodal and geographically structured. Existing approaches often rely on static map representations or single-modality sensor inputs, which fail to capture the richness of geographic context and the variability of real-world scenes. This paper introduces GeoWorldSim, a cross-modal geographic world modeling framework that integrates satellite imagery, street-level panoramas, LiDAR point clouds, and textual semantic labels through a diffusion-based spatial scene generation mechanism. The system constructs a unified, updatable world model that enables embodied agents to simulate plausible future views from unvisited viewpoints, thereby improving navigation robustness under occlusion, sensor noise, and environmental change. We present the architectural principles of GeoWorldSim, focusing on the trade-offs between geometric accuracy and perceptual realism, the governance of geospatial data fidelity across scales, and the policy implications of deploying such models in public urban infrastructures. The diffusion backbone is conditioned on geographic coordinates and partial observations, allowing the generation of spatially consistent scenes without requiring dense supervision. We discuss the sustainability of training such large-scale models, the fairness implications of geographic coverage biases, and the robustness of generated scenes under distribution shift. Through analytical case studies and cross-domain comparisons with prior world modeling systems, we demonstrate that GeoWorldSim offers a scalable and principled foundation for next-generation embodied navigation in urban environments. The paper concludes with forward-looking perspectives on the integration of geospatial world models with real-time edge computing and civic data governance frameworks.